(3HQGgjf GdYbhd aj cTa CSQGQ JgPjH GdCUhds - (3GdThjgj, GdMejOj, GdfLaj, GdMScj, GdMdj, eMeO Hf jhfS Hf QGVj, J (B1240(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3hGdhShGS Yf GdLgGd hGdTcGc hCYhGe GdfGS hhGLH Ydjge GdbVGA HGdCMcGe(B...s
(3BNQgG (B:s
(3GdebGe GdChd(B: (3Cf GdMce GdeYdb Ydi GdhUa EPG cGf YdI gd jdRe ef fajg faj GdMce ChdG ajg NdGas
(3JHUQI GdYfhGf (B:s
(3aj GdCYdGe(B: (3HQGgjf GdYbhd aj TQM JgPjH GdGUhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B160s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B197s
(3GdCYdGe(B: (3L(B7(3, U(B160s
Keywords: (3CUhd Gdabgs